2016
DOI: 10.1080/10245332.2016.1201630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and cumulative 5-year incidence of chronic lymphocytic leukemia in the adult population in the Russian Federation and Ukraine: Data from the LEUKOSPECT study

Abstract: The results of this study show diverse CLL incidence and prevalence patterns in the adult population of the Russian Federation and Ukraine. Authors propose a more comprehensive study with large region involvement to provide a more precise description of the incidence and prevalence of CLL in Eastern European countries and to better understand disparities reported versus the USA and other Western countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite previously described epidemiological differences in Chronic Lymphocytic Leukemia (CLL) incidence and prognosis, [1][2][3][4] CLL has not been assessed in larges series in multicultural developing countries.…”
Section: Chronic Lymphocytic Leukemia In Brazil: a Retrospective Analmentioning
confidence: 99%
“…Despite previously described epidemiological differences in Chronic Lymphocytic Leukemia (CLL) incidence and prognosis, [1][2][3][4] CLL has not been assessed in larges series in multicultural developing countries.…”
Section: Chronic Lymphocytic Leukemia In Brazil: a Retrospective Analmentioning
confidence: 99%
“…117047) was the first epidemiologic study of CLL in these post-Soviet countries. The first part of the study was aimed at assessing the prevalence (in 2013) and cumulative 5-year (2009–2013) incidence of CLL; these data were published in a separate manuscript 6 and will not be discussed further here. This paper focusses on the investigation of SoC, health care resource utilization, and DMCs in 2013 in the adult populations of cities across three post-Soviet countries – the Russian Federation (Russia), Ukraine, and Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, CLL was the most common type of mature B cell neoplasm (68%) and this was consistent with that documented in Baghdad 13 and Turkey 14 that confirmed CLL frequencies of 65.9%, 72.8% respectively The median age at diagnosis in the current study was 57.5 years with a peak incidence between 41 to 60 years which was close to that recorded previously in Erbil (65 years), 15 Baghdad (61 years) 13 and turkey (64.4 years). 14 In Western countries, on the other hand, the median age at diagnosis is more with a range (67 -72 years), 16 Male dominance has been found in the current study (66.2%) with male to female ratio of (1.95/1) which was accordance with the results of Hasan et al, 15 Hellek et al 17 and Padaro et al 18 In the present study the clinical symptoms of easy fatigability (50%), lymphadenopathy (41.2%), splenomegaly (41.2%), joint pain (30.9%), abdominal pain (29.4%), fever (26.5%) were the most presenting symptoms of CLL, and these symptoms were documented less frequently in the present study compared with previous study done in Erbil, 15 which recorded splenomegaly as most frequent clinical features (64.8%), lymphadenopathy(60%) and hepatomegaly (21.9%), a study done in Baghdad found that the most presenting features were lymphadenopathy (50%) followed by splenomegaly (35%), pallor (30%), hepatomegaly (22%) and fever (20%), 13 however, Previous studies have been well recorded the diversity of clinical presentations in CLL and their associations with ethnic background. 19,20 According to the literature, 30-35% of CLL cases were diagnosed accidentally, 21 however the current study reported (17.6%) of patients were diagnosed accidentally, probably due to late-stage disease presentation, deficiencies in the referring system, and a loss of regular health checkup behavior in our population.…”
mentioning
confidence: 99%